Spatial mapping and determinants of health performance in North Sumatra province - Rindayati, Wiwiek; Hastuti, Ing Mariani; Asmara, Alla (Jurnal Ekonomi & Studi Pembangunan, 2023)
The province of North Sumatra has the lowest health performance in Sumatra, with disparities amongst districts /cities. This study aims to analyze the health performance factor of North Sumatra districts/cities using a Geographically Weighted Panel Regression (GWPR) model analysis in 33 districts/cities with a time series of 2012-2019. The analysis results showed that the determinants of health performance differed between districts/cities grouped into 15 groups based on influencing factors and four clusters based on the area of the development areas. The income variable has a significant positive effect on all 33 districts, the education variable has a positive effect on 19 districts, the human health resources variable has a positive effect on 12 districts, the immunization variable has a positive effect on 11 districts, the proper sanitation variable has positive on nine districts, the government spending in health sector variable has positive on five districts, and the medical facility variable has positive on one district namely Karo. Determinants in the Nias Island Area: income, government spending in the health sector, and human resources. West Coast area: income, education, and proper sanitation. East Coast Area: income, education, health, human resources, and immunization. The determinant Highland area differs between regencies/cities. To improve the performance of health development in the province, it is necessary to carry out a spatial approach based on cluster equations and influencing factors. Increased income, education, and human health resources must be prioritized in almost all district areas.